Peran Kewirausahaan Berbasis Digital Dalam Mengurangi Tingkat Pengangguran - Munthe, Yusnita Ulfah; Nawawi, Zuhrinal M. (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The creation of entrepreneurs is an alternative solution to various problems in society such as poverty and social inequality, increasing unemployment of productive age and dwindling energy supply reserves, all of which require creative and innovative actions. Entrepreneurs are people who are able to turn an opportunity into a profitable business, which is processed through creativity, innovation and uniqueness in making a product and dare to take all possible risks that accompany it and do not make it easy to give up if they fail in building the business. In this case, the author examines that entrepreneurship participates in national development, digital-based entrepreneurship utilizes increasingly sophisticated technology, digital-based entrepreneurship as a solution to reducing unemployment rates, the large number of unemployed in Indonesia, entrepreneurship is something that must be instilled by young people and the Indonesian people. Keywords: Entrepreneurship, Digital, Unemployment.